Perubahan Tutupan Lahan Dampak dari Industri Nikel di Bahodopi Sulawesi Tengah - Gildha Eka Putri; I Dewa Made Frendika Septanaya (Dinasti Research, 2026)
The rapid development of the nickel industry in Bahodopi District, Morowali Regency, Central Sulawesi, has significantly transformed land use patterns due to the expansion of industrial areas and their supporting activities. This study aims to analyze land cover changes resulting from the development of the nickel industry in the area using a multitemporal approach covering the period from 2014 to 2025. The research employed a quantitative approach using spatial analysis based on Geographic Information Systems (GIS) through overlay techniques of land use maps from 2014, 2017, 2021, and 2025, combined with land use and land cover change analysis. The study area covers seven villages, namely Bahodopi, Keurea, Bahomakmur, Fatufia, Labota, Makarti Jaya, and Padabaho. The results indicate that industrial land experienced the highest increase across all study villages, particularly in Labota Village (5,449%), Makarti Jaya Village (4,656%), and Bahomakmur Village (2,058%). This increase was accompanied by substantial residential expansion, exceeding 1,000% in Bahodopi Village. In contrast, green areas and agricultural land declined in most parts of the study area due to their conversion into industrial zones, residential areas, and infrastructure. The dominant land conversion pattern was the transformation of green areas into industrial and residential land. This study concludes that the development of the nickel industry has been the primary driver of land cover change and spatial transformation in Bahodopi District, leading to an increasingly industrialized regional structure.